The Use of Story’ Retelling Technique to Develop Students’ Vocabulary at the Tenth Grade of SMAN 6 Wajo - Ulviana Rasni; Maemuna Muhayyang; A. Muliati (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study aims to find out the development of vocabulary mastery by using a story' retelling technique. The researchers used a quantitative method with a pre- experimental research design and used cluster random sampling. The sample of this research is class X MIPA Tahfidz, with 34 students. The instrument used is a vocabulary test (pretest and post-test) that aims to obtain data in this research. The results of the data analysis showed that with the use of story' retelling techniques, students' vocabulary mastery increased. It can be proven by the t test value was lower than P (0.000 ˂ 0.05), which means (H0) of this research was rejected and (H1) was accepted. Therefore, it is concluded that the use of the story' retelling technique can develop the vocabulary mastery of the tenth-grade students of SMAN 6 Wajo.